Linking Untargeted Metabolomics to Functional Bioactivity in Nutmeg (Myristica fragrans Houtt.): Current Advances, Bioactivity Integration, and Analytical Challenges - Susilo Susilo; Ratna Yuniarti; Titin Siswantining; Yasman Yasman (Journal of Biotropical Research and Nature Technology, 2026)
Myristica fragrans Houtt. has been widely explored due to its high chemical composition and many functional features, nevertheless, the analytical framework applied to analyze this species has progressed unevenly. This study critically discusses the shift from conventional GC–MS-based phytochemical profiling to more integrated metabolomics techniques incorporating LC-HRMS, chemometrics, and bioactivity analysis in nutmeg research. A literature study was undertaken in five scientific databases using PRISMA guidance. Studies were categorized as MAIN and SUPPORT to distinguish between metabolomics-driven studies and studies providing complementary evidence of phytochemical and bioactivity data. The synthesis illustrates that most of the published work still depends on GC–MS analysis of volatile fractions and essential oils, but fully untargeted metabolomics investigations are rare. Recent developments have increased metabolite coverage, sample discrimination and helped identification of potential markers related to bioactivity interpretation, species authentication and quality assessment. Most studies still tend to report relationships between metabolites and bioactivity mostly as compositional or statistical associations, biomarker verification remains patchy across the literature and metabolite annotation is still often limited to MSI Level 2 or 3, although examples of higher-confidence identification are emerging. In sum, contemporary M. fragrans research can best be characterized as a shift from extended phytochemical profiling to more biologically interpretable metabolomics. Future advances will depend on increased standardization, more confident metabolite annotation, stricter chemometric validation, and wider integration of chemical signatures with functional biological evidence to enable more robust and translatable applications of nutmeg metabolomics.